Polyvinylidene fluoride dielectric composite material, composite film and preparation method thereof
By introducing thermogenic liquid crystal polymers and maleic anhydride grafted polypropylene into polyvinylidene fluoride dielectric materials, combined with modified molybdenum disulfide, the mechanical properties and processing properties of dielectric materials when improving dielectric constants are solved. Taking into account both the problems, high dielectric constant, low dielectric loss and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202411503623.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-17
AI Technical Summary
While the existing polyvinylidene fluoride dielectric materials increase the dielectric constant, it is difficult to maintain good mechanical properties and processing properties, especially the problem of high dielectric loss after the increase of filler.
Introducing thermogenic liquid crystal polymers and maleic anhydride graft modified polypropylene into polyvinylidene fluoride polymers to form microfiber structures and similar network structures, improve tensile strength and interface adhesion, and modify two Molybdenum sulfide improves compatibility, prevents filler aggregation and reduces dielectric loss.
The dielectric constant and dielectric strength of polyvinylidene fluoride-based dielectric composite materials are significantly improved, while maintaining excellent mechanical properties and processing properties. The tensile strength reaches more than 33MPa, the dielectric constant reaches 23, and the dielectric loss is reduced.
Smart Images

Figure CN119320540A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of dielectric films, and in particular relates to a polyvinylidene fluoride-based dielectric composite material, and further relates to a dielectric composite film and a preparation method thereof. Background Art
[0002] Capacitors account for 60-80% of electronic systems, so the development of new dielectric materials with high dielectric constants has become an important development area in the electronic materials industry. Usually, it is difficult for a single component to simultaneously meet excellent dielectric properties and processability. Therefore, polymer and inorganic filler composites have become a hot topic in current dielectric material research.
[0003] Due to its good piezoelectric properties, mechanical properties and high heat resistance, polyvinylidene fluoride has been widely used in underwater acoustics, ultrasound, transducers and sensors. However, the low dielectric constant of polyvinylidene fluoride seriously restricts its application in the field of high-end electronic technology. At present, researchers usually use inorganic ceramics, conductive fillers or metal particles to fill composites in the hope of obtaining composite dielectric materials with high dielectric and low loss properties. In order to increase the dielectric constant of the material, it is necessary to increase the amount of inorganic filler added, but too much inorganic filler will cause the mechanical properties of the dielectric material to decrease. Therefore, how to balance mechanical properties, dielectric properties and processing properties is an urgent problem to be solved. Summary of the invention
[0004] The present invention is based on the inventor's discovery and understanding of the following facts and problems: In the related art, CN113214580A discloses a fluorine-containing polymer dielectric composite material and a preparation method thereof, wherein the composite material is prepared by melt blending a fluorine-containing polymer, a polymer compatibilizer, modified molybdenum disulfide and modified hollow glass microspheres in a certain proportion. Although the dielectric properties of the dielectric material are significantly improved, the melt has a high apparent viscosity during processing, and the melt is easily broken when extruded at high speed, which affects the improvement of product quality. CN118027582A discloses a novel easy-to-process fluorine-containing polymer dielectric composite material, wherein the composite material is prepared by melt blending a fluorine-containing polymer, a long-chain branched polyolefin elastomer, modified molybdenum disulfide and modified hollow glass microspheres. While maintaining a relatively high dielectric constant, the flexibility and processing properties of the dielectric composite material are also significantly improved, but the addition of elastomers and inorganic fillers will inevitably sacrifice a portion of the mechanical strength of the fluorine-containing polymer matrix. Therefore, it is necessary to conduct in-depth research on dielectric composites to improve their dielectric constant while maintaining their good mechanical properties and processing properties.
[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, an embodiment of the present invention provides a polyvinylidene fluoride-based dielectric composite material, which not only improves the tensile strength and processing performance of the composite material, but also improves the dielectric constant and dielectric strength of the composite material, and reduces the dielectric loss by introducing a thermotropic liquid crystal polymer into the material.
[0006] The embodiment of the present invention provides a polyvinylidene fluoride-based dielectric composite material, comprising a polyvinylidene fluoride polymer, a thermotropic liquid crystal polymer, modified molybdenum disulfide and maleic anhydride grafted modified polypropylene.
[0007] Advantages and technical effects brought by the polyvinylidene fluoride based dielectric composite material of the embodiment of the present invention:
[0008] 1. In the embodiment of the present invention, a polyvinylidene fluoride based polymer is used as a matrix material, and a thermotropic liquid crystal polymer and maleic anhydride grafted modified polypropylene are introduced at the same time. The thermotropic liquid crystal polymer is a semi-aromatic thermotropic liquid crystal copolyester, and a macromolecular chain with a linear structure is formed by connecting a mesogen unit with a flexible polymethylene chain. When subjected to external shearing force, the macromolecular chain can be arranged and oriented along the direction of the external force to form a microfiber structure with a large aspect ratio. The formed microfibers remain inside the material after cooling, and can play a self-reinforcement role, showing excellent processing performance and mechanical properties. After the polyvinyl fluoride polymer is modified by polypropylene, the anhydride active groups react with the liquid crystal polymer macromolecules and the polyvinyl fluoride polymer matrix, thereby improving the interfacial adhesion and making the microfibers molecularly connected, forming a network-like structure, thereby significantly improving the tensile strength; at the same time, the rigid liquid crystal unit in the liquid crystal polymer makes the liquid crystal molecular chain have the characteristics of spontaneous orientation, and it is very easy to arrange in parallel along the long axis direction under shearing, and there is little entanglement between the chains, so the flow properties in the molten state are very similar to those of the liquid, and the shear resistance is very small, so the melt viscosity is low and has excellent fluidity. In the embodiment of the present invention, by introducing the liquid crystal polymer into the polyvinyl fluoride polymer matrix, not only is the polyvinyl fluoride polymer matrix given a more excellent tensile strength, but also its processing performance is effectively improved, so that the tensile strength of the composite material can reach more than 33MPa, and the critical shear rate of each raw material in the polyvinyl fluoride dielectric composite material at melt fracture after mixing reaches 95S -1 Above, the melt torque drops below 41.3Nm;
[0009] 2. In the embodiment of the present invention, modified molybdenum disulfide is introduced into the composite material. After the molybdenum disulfide filler is functionalized, its compatibility with the polyvinylidene fluoride based polymer matrix is significantly improved. At the same time, the liquid crystal polymer is subjected to strong shearing when it is melted to form microfibers. These microfibers have a relatively large length diameter and are interspersed between the molybdenum disulfide layers with a sandwich structure, thereby expanding the interlayer spacing and effectively preventing the aggregation of molybdenum disulfide. The polyvinylidene fluoride based polymer matrix and the molybdenum disulfide filler can be mixed more evenly, thus solving the problem in the prior art that the dielectric loss is high due to the agglomeration of the filler. The dielectric constant and dielectric strength of the composite material are effectively improved. At the same time, the crystallization of the polymer melt occurs during the cooling process, which is also the process in which the liquid crystal unit is oriented in the shear direction to form microfibers. Because the crystallization process is the result of the combined action of the nucleus growth process and the chain diffusion process, the thermotropic liquid crystal polymer plays a role of heterogeneous nucleation, and does not hinder the diffusion of the chain. The crystallization ability is improved, which effectively improves the dielectric properties of the composite material, so that the dielectric strength of the dielectric composite material can reach more than 160KV / mm, and the dielectric constant can reach more than 23.
[0010] In some embodiments, the thermotropic liquid crystal polymer includes at least one of Xydar, Vectra, Ueno and Rodrun. Optionally, the thermotropic liquid crystal polymer includes at least one of Rodrun LC-5000, Rodrun LC-3000 or Ueno LCP2000.
[0011] In some embodiments, the mass percentage of the thermotropic liquid crystal polymer is 0.5-12%.
[0012] In some embodiments, the polyvinylidene fluoride-based polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-tetrafluoroethylene copolymer, or polyvinylidene fluoride-hexafluoropropylene copolymer.
[0013] In some embodiments, the modified molybdenum disulfide is prepared by modifying molybdenum disulfide using a γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent.
[0014] In some embodiments, the maleic anhydride grafted modified polypropylene has a melt flow rate of 1 to 12 g / 10 min at 230° C. and 3.8 kg.
[0015] In some embodiments, in the dielectric composite material, the mass percentage of the polyvinylidene fluoride based polymer is 65-95%, the mass percentage of the modified molybdenum disulfide is 1-10%, and the mass percentage of the maleic anhydride grafted modified polypropylene is 0.5-15%.
[0016] The embodiment of the present invention further provides a polyvinylidene fluoride-based dielectric composite film, which is prepared using the dielectric composite material of the embodiment of the present invention.
[0017] The polyvinylidene fluoride-based dielectric composite film of the embodiment of the present invention has all the advantages that can be brought by the dielectric composite material of the embodiment of the present invention, which will not be elaborated here.
[0018] In some embodiments, the dielectric composite material is prepared by melt blending and extrusion to obtain a polyvinylidene fluoride-based dielectric composite film.
[0019] The embodiment of the present invention also provides a method for preparing a polyvinylidene fluoride-based dielectric composite film, comprising: mixing and granulating a polyvinylidene fluoride-based polymer, a thermotropic liquid crystal polymer, maleic anhydride-modified polypropylene and modified molybdenum disulfide in a designed ratio, and preparing the dielectric composite film through extrusion, stretching and casting.
[0020] The method for preparing the polyvinylidene fluoride-based dielectric composite film in the embodiment of the present invention has a simple process and low cost, and can make full use of the raw materials. The prepared dielectric composite film not only has excellent tensile strength and processing performance, but also has a high dielectric constant and dielectric strength, while maintaining low dielectric loss.
[0021] In some embodiments, the preparation method of the modified molybdenum disulfide includes: adding molybdenum disulfide to a hydrogen peroxide solution for surface hydroxylation treatment, then adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent for ultrasonic treatment, and obtaining modified molybdenum disulfide after drying.
[0022] In some embodiments, the mixing is performed in a high-speed mixer with a controlled rotation speed of 80 to 300 r / ppm for a time of 1 to 5 minutes.
[0023] In some embodiments, the granulation is carried out in a twin-screw extruder, and the temperature of each zone is set as follows: the temperature of the first zone is: 110-140°C, the temperature of the second zone is: 150-180°C, the temperature of the third zone is: 170-230°C, and the temperature of the fourth zone is: 210-260°C.
[0024] In some embodiments, the extrusion is carried out in a single-screw extruder, and the temperature of each zone is set as follows: the temperature of the first zone is 110-150°C, the temperature of the second zone is 150-200°C, the temperature of the third zone is 190-240°C, and the temperature of the fourth zone is 200-260°C; the stretching ratio is 1-8; and the temperature of the casting roller in the casting process is 70-100°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The curves of melt torque variation over time after mixing various raw materials of polyvinylidene fluoride-based dielectric composite materials prepared in various embodiments and comparative examples are shown. DETAILED DESCRIPTION
[0026] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0027] A polyvinylidene fluoride-based dielectric composite material according to an embodiment of the present invention comprises a polyvinylidene fluoride polymer, a thermotropic liquid crystal polymer, modified molybdenum disulfide and maleic anhydride grafted modified polypropylene, wherein the mass percentage of the thermotropic liquid crystal polymer in the dielectric composite material is 0.5-12%.
[0028] In the polyvinylidene fluoride vinyl-based dielectric composite material of the embodiment of the present invention, the polyvinylidene fluoride vinyl polymer is used as the matrix material, and the thermotropic liquid crystal polymer and maleic anhydride grafted modified polypropylene are introduced at the same time. The thermotropic liquid crystal polymer polymer chain contains rigid mesogen units and flexible spacers. When subjected to external shearing, it can be arranged and oriented along the direction of the external force to form a microfiber structure with a large aspect ratio. The formed microfibers remain inside the material after cooling, and can play a self-reinforcement role, showing excellent processing performance and mechanical properties; after the polyvinylidene fluoride vinyl-based polymer is modified by the liquid crystal polymer and maleic anhydride grafted polypropylene, the anhydride active group reacts with the liquid crystal polymer macromolecule and the polyvinylidene fluoride vinyl polymer matrix, thereby improving the interfacial adhesion, so that the microfibers are molecularly connected to form a network-like structure, thereby significantly improving the tensile strength; at the same time, the rigid liquid crystal unit in the liquid crystal polymer makes the liquid crystal molecular chain have the characteristics of spontaneous orientation, and it is very easy to be arranged in parallel along the long axis direction under shearing, and there is little entanglement between the chains, so the flow performance in the molten state is very similar to that of the liquid, and the shear resistance is very small, so the melt viscosity is low, and it has excellent fluidity. In the embodiment of the present invention, by introducing liquid crystal polymer into the polyvinylidene fluoride based polymer matrix, not only the polyvinylidene fluoride based polymer matrix is endowed with more excellent tensile strength, but also its processing performance is effectively improved, so that the tensile strength of the composite material can reach more than 33MPa, and the critical shear rate of each raw material in the polyvinylidene fluoride based dielectric composite material during melt fracture after mixing reaches 95S -1 Above, the melt torque drops below 41.3Nm.
[0029] In the polyvinylidene fluoride based dielectric composite material of the embodiment of the present invention, modified molybdenum disulfide is introduced. After the molybdenum disulfide filler is functionalized, its compatibility with the polyvinylidene fluoride based polymer matrix is significantly improved. At the same time, the liquid crystal polymer is subjected to a strong shearing effect when it is melted to form microfibers. These microfibers have a relatively large aspect ratio and are interspersed between the molybdenum disulfide layers with a sandwich structure, thereby expanding the interlayer spacing and effectively preventing the aggregation of molybdenum disulfide. The polyvinylidene fluoride based polymer matrix and the molybdenum disulfide filler can be mixed more evenly, thereby solving the problem in the prior art that the dielectric loss is easily biased due to the agglomeration of the filler. The problem of high dielectric constant and dielectric strength is effectively improved; at the same time, the crystallization of the polymer melt occurs during the cooling process, which is also the process of liquid crystal units orienting in the shear direction to form microfibers. Because the crystallization process is the result of the combined action of the nucleus growth process and the chain diffusion process, the thermotropic liquid crystal polymer plays a role of heterogeneous nucleation, and does not hinder the diffusion of the chain. The crystallization ability is improved, which effectively improves the dielectric properties of the composite material, so that the dielectric strength of the dielectric composite material can reach more than 160KV / mm, and the dielectric constant can reach more than 23.
[0030] In some embodiments, the thermotropic liquid crystal polymer includes at least one of Xydar, Vectra, Ueno and Rodrun, preferably the Rodrun series.
[0031] In some embodiments, the thermotropic liquid crystal polymer includes at least one of Rodrun LC-5000, Rodrun LC-3000 or Ueno LCP 2000. In the embodiments of the present invention, the use of the preferred thermotropic liquid crystal polymer is conducive to giving full play to the role of the thermotropic liquid crystal polymer and further improving the mechanical properties, processing properties and dielectric properties of the composite material.
[0032] In some embodiments, the mass percentage of the thermotropic liquid crystal polymer is 0.5-12%, such as 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, etc., preferably 1-10%, more preferably 3-8%. In the embodiment of the present invention, the content of the thermotropic liquid crystal polymer in the composite material is further optimized, which is conducive to giving the composite material better comprehensive properties. If the amount of thermotropic liquid crystal polymer added is too much, it is not conducive to improving the compatibility with the PVDF-based polymer, resulting in a certain degree of phase separation, which is not conducive to improving the tensile strength. If the amount of thermotropic liquid crystal polymer added is too little, the reinforcement effect of spontaneous fiberization is not obvious.
[0033] In some embodiments, the polyvinylidene fluoride based polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-tetrafluoroethylene copolymer or polyvinylidene fluoride-hexafluoropropylene copolymer. In the embodiments of the present invention, there is no particular limitation on the polyvinylidene fluoride based polymer, and the polyvinylidene fluoride based polymer commonly used in the prior art can be used as the polymer matrix of the embodiments of the present invention.
[0034] In some embodiments, the modified molybdenum disulfide is modified by using γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent. In the embodiment of the present invention, the molybdenum disulfide is modified by using a silane coupling agent, which is beneficial to improve the compatibility of molybdenum disulfide and the polyvinylidene fluoride based polymer matrix, thereby improving the dielectric properties of the composite material.
[0035] In some embodiments, the maleic anhydride grafted modified polypropylene has a melt flow rate of 1 to 12 g / 10 min at 230° C. and 3.8 kg. In the embodiments of the present invention, the introduction of the selected maleic anhydride grafted modified polypropylene into the composite material is conducive to the reaction of the anhydride active groups with the liquid crystal polymer macromolecules and the polyvinylidene fluoride based polymer matrix, further improving the interfacial adhesion, thereby improving the tensile strength of the composite material.
[0036] In some embodiments, in the dielectric composite material, the mass percentage of the polyvinylidene fluoride based polymer is 65-95%, the mass percentage of the modified molybdenum disulfide is 1-10%, and the mass percentage of the maleic anhydride grafted modified polypropylene is 0.5-15%. In the embodiments of the present invention, the content of each substance in the composite material is optimized, which is conducive to the interaction between the substances and further improves the mechanical properties, dielectric properties and processing properties of the composite material.
[0037] The embodiment of the present invention further provides a polyvinylidene fluoride-based dielectric composite film, which is made using the dielectric composite material of the embodiment of the present invention. The dielectric composite film of the embodiment of the present invention has all the advantages of the dielectric composite material of the embodiment of the present invention, which will not be described in detail here.
[0038] In some embodiments, the dielectric composite material is prepared by melt blending and extrusion to obtain a polyvinylidene fluoride-based dielectric composite film.
[0039] The embodiment of the present invention also provides a method for preparing a polyvinylidene fluoride-based dielectric composite film, comprising: mixing and granulating a polyvinylidene fluoride-based polymer, a thermotropic liquid crystal polymer, maleic anhydride-modified polypropylene and modified molybdenum disulfide in a designed ratio, and preparing the dielectric composite film through extrusion, stretching and casting.
[0040] The method for preparing the polyvinylidene fluoride-based dielectric composite film in the embodiment of the present invention has a simple process and low cost, and can make full use of the raw materials. The prepared dielectric composite film not only has excellent tensile strength and processing performance, but also has a high dielectric constant and dielectric strength, while maintaining low dielectric loss.
[0041] In some embodiments, the preparation method of the modified molybdenum disulfide comprises: adding molybdenum disulfide to a hydrogen peroxide solution for surface hydroxylation treatment, then adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent for ultrasonic treatment, and drying to obtain modified molybdenum disulfide. In the method of the embodiment of the present invention, the molybdenum disulfide is first subjected to hydrogen peroxide hydroxylation treatment, and then subjected to modification treatment with a silane coupling agent, which is beneficial to further improve the compatibility of the molybdenum disulfide with the matrix polyvinylidene fluoride polymer, thereby improving the dielectric properties of the composite material.
[0042] In some embodiments, the mixing is performed in a high-speed mixer, with a controlled speed of 80 to 300 r / ppm and a time of 1 to 5 minutes;
[0043] In some embodiments, the granulation is carried out in a twin-screw extruder, and the temperature of each zone is set as follows: the temperature of the first zone is: 110-140°C, the temperature of the second zone is: 150-180°C, the temperature of the third zone is: 170-230°C, and the temperature of the fourth zone is: 210-260°C.
[0044] In some embodiments, the extrusion is carried out in a single-screw extruder, and the temperature of each zone is set as follows: the temperature of the first zone is 110-150°C, the temperature of the second zone is 150-200°C, the temperature of the third zone is 190-240°C, and the temperature of the fourth zone is 200-260°C; the stretching ratio is 1-8; and the temperature of the casting roller in the casting process is 70-100°C.
[0045] The present invention is described in detail below with reference to the embodiments and the accompanying drawings.
[0046] Example 1
[0047] (1) Preparation of modified molybdenum disulfide
[0048] Molybdenum disulfide is added to a hydrogen peroxide solution with a mass concentration of 25%, wherein the mass ratio of the molybdenum disulfide to the hydrogen peroxide solution is 4g:80ml, magnetic stirring is performed, the rotation speed is controlled to be 45r / min, stirring is performed for 16 hours, and a solid product is obtained after filtration. The solid product is placed in an oven at 100°C and dried for 24 hours to obtain oxidized molybdenum disulfide; then the solid product is added to a γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent and ultrasonically treated and shaken for 8 hours, and then placed in an oven after filtration and dried at 120°C to obtain modified molybdenum disulfide.
[0049] (2) Preparation of mixed materials for polyvinylidene fluoride based dielectric composites
[0050] Polyvinylidene fluoride-trifluoroethylene copolymer, thermotropic liquid crystal polymer Rodrun LC-5000 (Unica Co., Ltd., Japan), maleic anhydride modified polypropylene and modified molybdenum disulfide were added to a high-speed mixer and mixed evenly, the speed of the high-speed mixer was 300RPM, and the mixing time was 1 minute. Then, they were added to a twin-screw extruder for granulation, and the temperature of each zone of the twin-screw extruder was set as follows: the temperature of the first zone: 140°C, the temperature of the second zone: 180°C, the temperature of the third zone: 230°C, and the temperature of the fourth zone: 260°C, and the granulation was set aside.
[0051] (3) Preparation of polyvinylidene fluoride-based dielectric composite films
[0052] The granulated polyvinylidene fluoride based dielectric composite material was extruded, stretched and casted by a single screw extruder to prepare a composite film, with the temperature of the first zone being 150°C, the temperature of the second zone being 200°C, the temperature of the third zone being 240°C, and the temperature of the fourth zone being 260°C. The stretching ratio was 8, and the temperature of the casting roller was 100°C.
[0053] In the polyvinylidene fluoride-based dielectric composite film prepared in this embodiment, the mass percentage of thermotropic liquid crystal polymer is 0.5%, the mass percentage of modified molybdenum disulfide is 1%, and the mass percentage of maleic anhydride-modified polypropylene is 5%.
[0054] Example 2
[0055] (1) Preparation of modified molybdenum disulfide
[0056] Molybdenum disulfide is added to a hydrogen peroxide solution with a mass concentration of 25%, wherein the mass ratio of the molybdenum disulfide to the hydrogen peroxide solution is 4g:80ml, magnetic stirring is performed, the rotation speed is controlled to be 45r / min, stirring is performed for 16 hours, and a solid product is obtained after filtration. The solid product is placed in an oven at 100°C and dried for 24 hours to obtain oxidized molybdenum disulfide; then the solid product is added to a γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent and ultrasonically treated and shaken for 8 hours, and then placed in an oven after filtration and dried at 120°C to obtain modified molybdenum disulfide.
[0057] (2) Preparation of mixed materials for polyvinylidene fluoride based dielectric composites
[0058] Polyvinylidene fluoride-tetrafluoroethylene copolymer, thermotropic liquid crystal polymer Rodrun LC-5000 (Unica Co., Ltd., Japan), maleic anhydride modified polypropylene and modified molybdenum disulfide were added to a high-speed mixer and mixed evenly, the speed of the high-speed mixer was 80RPM, and the mixing time was 5 minutes. Then, they were added to a twin-screw extruder for granulation, and the temperature of each zone of the twin-screw extruder was set as follows: the temperature of the first zone: 110°C, the temperature of the second zone: 150°C, the temperature of the third zone: 170°C, and the temperature of the fourth zone: 210°C, and the granulation was set aside.
[0059] (3) Preparation of polyvinylidene fluoride-based dielectric composite films
[0060] The granulated polyvinylidene fluoride-based dielectric composite material was extruded, stretched and cast using a single screw extruder to prepare a composite film, with the first zone temperature being 110°C, the second zone temperature being 150°C, the third zone temperature being 190°C, and the fourth zone temperature being 200°C. The stretching ratio was 1, and the temperature of the casting roller was 70°C.
[0061] In the polyvinylidene fluoride-based dielectric composite film prepared in this embodiment, the mass percentage of thermotropic liquid crystal polymer is 1.5%, the mass percentage of modified molybdenum disulfide is 3%, and the mass percentage of maleic anhydride-modified polypropylene is 15%.
[0062] Example 3
[0063] (1) Preparation of modified molybdenum disulfide
[0064] Molybdenum disulfide is added to a hydrogen peroxide solution with a mass concentration of 25%, wherein the mass ratio of the molybdenum disulfide to the hydrogen peroxide solution is 4g:80ml, magnetic stirring is performed, the rotation speed is controlled to be 45r / min, stirring is performed for 16 hours, and a solid product is obtained after filtration. The solid product is placed in an oven at 100°C and dried for 24 hours to obtain oxidized molybdenum disulfide; then the solid product is added to a γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent and ultrasonically treated and shaken for 8 hours, and then placed in an oven after filtration and dried at 120°C to obtain modified molybdenum disulfide.
[0065] (2) Preparation of mixed materials for polyvinylidene fluoride based dielectric composites
[0066] Polyvinylidene fluoride-hexafluoropropylene copolymer, thermotropic liquid crystal polymer Rodrun LC-5000 (Unica Co., Ltd., Japan), maleic anhydride modified polypropylene and modified molybdenum disulfide were added to a high-speed mixer and mixed evenly, the speed of the high-speed mixer was 150RPM, and the mixing time was 5 minutes. Then, they were added to a twin-screw extruder for granulation, and the temperature of each zone of the twin-screw extruder was set as follows: the temperature of the first zone: 120°C, the temperature of the second zone: 160°C, the temperature of the third zone: 210°C, and the temperature of the fourth zone: 245°C, and the granulation was set aside.
[0067] (3) Preparation of polyvinylidene fluoride-based dielectric composite films
[0068] The granulated polyvinylidene fluoride-based dielectric composite material was extruded, stretched and cast using a single screw extruder to prepare a composite film, with the first zone temperature at 150°C, the second zone temperature at 200°C, the third zone temperature at 240°C and the fourth zone temperature at 260°C. The stretching ratio was 4 and the temperature of the casting roller was 85°C.
[0069] In the polyvinylidene fluoride-based dielectric composite film prepared in this embodiment, the mass percentage of thermotropic liquid crystal polymer is 3%, the mass percentage of modified molybdenum disulfide is 5%, and the mass percentage of maleic anhydride-modified polypropylene is 10%.
[0070] Example 4
[0071] (1) Preparation of modified molybdenum disulfide
[0072] Molybdenum disulfide is added to a hydrogen peroxide solution with a mass concentration of 25%, wherein the mass ratio of the molybdenum disulfide to the hydrogen peroxide solution is 4g:80ml, magnetic stirring is performed, the rotation speed is controlled to be 45r / min, stirring is performed for 16 hours, and a solid product is obtained after filtration. The solid product is placed in an oven at 100°C and dried for 24 hours to obtain oxidized molybdenum disulfide; then the solid product is added to a γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent and ultrasonically treated and shaken for 8 hours, and then placed in an oven after filtration and dried at 120°C to obtain modified molybdenum disulfide.
[0073] (2) Preparation of mixed materials for polyvinylidene fluoride based dielectric composites
[0074] Polyvinylidene fluoride-trifluoroethylene copolymer, thermotropic liquid crystal polymer Rodrun LC-5000 (Unica Co., Ltd., Japan), maleic anhydride modified polypropylene and modified molybdenum disulfide were added to a high-speed mixer and mixed evenly, the speed of the high-speed mixer was 220RPM, and the mixing time was 3 minutes. Then, they were added to a twin-screw extruder for granulation, and the temperature of each zone of the twin-screw extruder was set as follows: the temperature of the first zone: 140°C, the temperature of the second zone: 180°C, the temperature of the third zone: 230°C, and the temperature of the fourth zone: 260°C, and the granulation was set aside.
[0075] (3) Preparation of polyvinylidene fluoride-based dielectric composite films
[0076] The granulated polyvinylidene fluoride based dielectric composite material was extruded, stretched and casted by a single screw extruder to prepare a composite film, with the temperature of the first zone being 150°C, the temperature of the second zone being 200°C, the temperature of the third zone being 240°C, and the temperature of the fourth zone being 260°C. The stretching ratio was 6, and the temperature of the casting roller was 100°C.
[0077] In the polyvinylidene fluoride-based dielectric composite film prepared in this embodiment, the mass percentage of thermotropic liquid crystal polymer is 8%, the mass percentage of modified molybdenum disulfide is 8%, and the mass percentage of maleic anhydride-modified polypropylene is 12%.
[0078] Example 5
[0079] (1) Preparation of modified molybdenum disulfide
[0080] Molybdenum disulfide is added to a hydrogen peroxide solution with a mass concentration of 25%, wherein the mass ratio of the molybdenum disulfide to the hydrogen peroxide solution is 4g:80ml, magnetic stirring is performed, the rotation speed is controlled to be 45r / min, stirring is performed for 16 hours, and a solid product is obtained after filtration. The solid product is placed in an oven at 100°C and dried for 24 hours to obtain oxidized molybdenum disulfide; then the solid product is added to a γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent and ultrasonically treated and shaken for 8 hours, and then placed in an oven after filtration and dried at 120°C to obtain modified molybdenum disulfide.
[0081] (2) Preparation of mixed materials for polyvinylidene fluoride based dielectric composites
[0082] Polyvinylidene fluoride-trifluoroethylene copolymer, thermotropic liquid crystal polymer Rodrun LC-5000 (Unica Co., Ltd., Japan), maleic anhydride modified polypropylene and modified molybdenum disulfide were added to a high-speed mixer and mixed evenly, the speed of the high-speed mixer was 280RPM, and the mixing time was 4 minutes. Then, they were added to a twin-screw extruder for granulation, and the temperature of each zone of the twin-screw extruder was set as follows: the temperature of the first zone: 140°C, the temperature of the second zone: 180°C, the temperature of the third zone: 230°C, and the temperature of the fourth zone: 260°C, and the granulation was set aside.
[0083] (3) Preparation of polyvinylidene fluoride-based dielectric composite films
[0084] The granulated polyvinylidene fluoride-based dielectric composite material was extruded, stretched and cast using a single screw extruder to prepare a composite film, with the first zone temperature at 150°C, the second zone temperature at 200°C, the third zone temperature at 240°C and the fourth zone temperature at 260°C. The stretching ratio was 4 and the temperature of the casting roller was 80°C.
[0085] In the polyvinylidene fluoride-based dielectric composite film prepared in this embodiment, the mass percentage of thermotropic liquid crystal polymer is 6%, the mass percentage of modified molybdenum disulfide is 10%, and the mass percentage of maleic anhydride-modified polypropylene is 10%.
[0086] Example 6
[0087] The method is the same as that of Example 5, except that the thermotropic liquid crystal polymer used is Rodrun LC-3000 (Unica Corporation, Japan).
[0088] Example 7
[0089] The method is the same as that of Example 5, except that the thermotropic liquid crystal polymer used is Ueno LCP 2000 (Ueno Pharmaceutical Co., Ltd., Japan).
[0090] Comparative Example 1
[0091] The method is the same as that of Example 1, except that the modified hollow glass microspheres are used to replace the thermotropic crystalline polymer, as follows:
[0092] (1) Preparation of modified molybdenum disulfide
[0093] Molybdenum disulfide is added to a hydrogen peroxide solution with a mass concentration of 25%, wherein the mass ratio of the molybdenum disulfide to the hydrogen peroxide solution is 4g:80ml, magnetic stirring is performed, the rotation speed is controlled to be 45r / min, stirring is performed for 16 hours, and a solid product is obtained after filtration. The solid product is placed in an oven at 100°C and dried for 24 hours to obtain oxidized molybdenum disulfide; then the solid product is added to a γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent and ultrasonically treated and shaken for 8 hours, and then placed in an oven after filtration and dried at 120°C to obtain modified molybdenum disulfide.
[0094] (2) Preparation of modified hollow glass microspheres
[0095] The hollow glass microspheres were added into maleic anhydride aqueous solution, and ammonium persulfate was used as an initiator. After the grafting reaction was carried out at 80-90°C for 6-8 hours, the ungrafted maleic anhydride monomer or its self-polymer was removed by ultrasonic treatment for 1 hour, and then washed with deionized water for several times. After filtering, the mixture was placed in a vacuum oven and dried at 100°C for 10 hours to obtain modified hollow glass microspheres.
[0096] (3) Preparation of mixed materials of polyvinylidene fluoride based dielectric composites
[0097] Add polyvinylidene fluoride-trifluoroethylene copolymer, modified hollow glass microspheres, maleic anhydride modified polypropylene and modified molybdenum disulfide into a high-speed mixer and mix them evenly. The speed of the high-speed mixer is 300RPM and the mixing time is 1 minute. Then add them into a twin-screw extruder for granulation. The temperature of each zone of the twin-screw extruder is set as follows: the temperature of the first zone is 140°C, the temperature of the second zone is 180°C, the temperature of the third zone is 230°C, and the temperature of the fourth zone is 260°C. Granulation is ready for use.
[0098] (4) Preparation of polyvinylidene fluoride-based dielectric composite films
[0099] The granulated polyvinylidene fluoride based dielectric composite material was extruded, stretched and casted by a single screw extruder to prepare a composite film, with the temperature of the first zone being 150°C, the temperature of the second zone being 200°C, the temperature of the third zone being 240°C, and the temperature of the fourth zone being 260°C. The stretching ratio was 8, and the temperature of the casting roller was 100°C.
[0100] In the polyvinylidene fluoride-based dielectric composite film prepared in this comparative example, the mass percentage of hollow glass microspheres is 0.5%, the mass percentage of modified molybdenum disulfide is 1%, and the mass percentage of maleic anhydride-modified polypropylene is 5%.
[0101] The dielectric composite materials and dielectric composite film samples prepared in each embodiment and comparative example were subjected to performance tests, and the dielectric strength, dielectric constant, dielectric loss, elongation at break, critical shear rate of melt fracture and melt torque of the samples were tested respectively. The test results are shown in Tables 1 and Figure 1 .in:
[0102] Dielectric constant and dielectric loss: Tested in accordance with national standard GB / T1409-2006, the sample is inserted into the electrode system for measurement. The electrode diameter is 30mm, the room temperature is 25℃, and the frequency range is 20Hz~106Hz.
[0103] Dielectric strength: Tested in accordance with the national standard GB / T1408-2006, using electrodes of different diameters, one of which has a diameter of 25mm and a height of about 25mm, and the other has a diameter of 75mm and a height of about 15mm. The film is subjected to a DC breakdown test, with a voltage rise rate of 100v / s, and at least 5 effective breakdown points are tested for each sample. The median of the test results is taken as the value of the dielectric strength. If any experimental result deviates from the median by more than 15%, another 5 tests are required, and then the median of the 10 tests is taken as the value of the dielectric strength.
[0104] Tensile strength: According to GB / T1040.2-2006 Determination of tensile properties of plastics. The tensile speed is 50mm / min.
[0105] Melt fracture critical shear rate: According to ASTM D3835-2016, the standard test method for determining the properties of polymer materials using a capillary rheometer, the larger the value of the melt fracture critical shear rate, the better the processing fluidity of the dielectric composite material. In the subsequent extrusion process, at the same processing temperature, a higher speed can be used for processing, thereby improving production efficiency and reducing costs.
[0106] Melt torque: tested by torque rheometer at a speed of 40RPM. The smaller the melt torque, the smaller the resistance to the composite melt during flow, the lower the energy consumption and the better the processing performance.
[0107] Table 1
[0108]
[0109] Through Table 1 and Figure 1 It can be seen that in Examples 1-7, by introducing the thermotropic liquid crystal polymer into the composite material, the thermotropic liquid crystal polymer interacts with the maleic anhydride grafted polypropylene and the polyvinylidene fluoride based polymer in the composite material, effectively improving the mechanical properties and processing properties of the composite material, so that the tensile strength of the composite material can reach more than 33 MPa, and the critical shear rate at melt fracture reaches 95S -1 At the same time, in Examples 1-7, the thermotropic liquid crystal polymer can change the interlayer spacing of molybdenum disulfide in the composite material, prevent the aggregation of molybdenum disulfide in the composite material, and effectively improve the dielectric properties of the composite film, so that the dielectric strength of the composite film of the embodiment of the present application can reach more than 160KV / mm, the dielectric constant can reach more than 23, and the dielectric loss can be controlled at 0.03 or less.
[0110] In Comparative Example 1, compared with Example 1, the main difference of the composite material is that modified hollow glass microspheres are introduced. Since the modified glass microspheres are inorganic fillers, although they have been modified, the interface bonding force between them and the PVDF matrix polymer is still relatively weak. The agglomeration of fillers causes the overall performance of the composite material to decrease, and the critical shear rate of the melt fracture of the composite material is reduced to 65S. -1 , the melt torque is increased to above 45.5 Nm, and the dielectric constant can only reach 11. However, in Example 1, the dielectric constant can reach 23 when only 0.5% of the thermotropic liquid crystal polymer is introduced.
[0111] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0112] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A polyvinylidene fluoride-based dielectric composite material, characterized in that: Including polyvinylidene fluoride based polymers, thermotropic liquid crystal polymers, modified molybdenum disulfide and maleic anhydride grafted modified polypropylene.
2. The polyvinylidene fluoride-based dielectric composite material according to claim 1, characterized in that: The thermotropic liquid crystal polymer comprises at least one of Xydar, Vectra, Ueno and Rodrun, Optionally, the thermotropic liquid crystal polymer comprises at least one of Rodrun LC-5000, Rodrun LC-3000 or Ueno LCP 2000; And / or, the mass percentage of the thermotropic liquid crystal polymer is 0.5-12%.
3. The polyvinylidene fluoride-based dielectric composite material according to claim 1, characterized in that: The polyvinylidene fluoride-based polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-tetrafluoroethylene copolymer or polyvinylidene fluoride-hexafluoropropylene copolymer; And / or, the modified molybdenum disulfide is prepared by modifying molybdenum disulfide using a γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent; And / or, the maleic anhydride grafted modified polypropylene has a melt flow rate of 1 to 12 g / 10 min at 230° C. and 3.8 kg.
4. The polyvinylidene fluoride-based dielectric composite material according to claim 1, characterized in that: In the dielectric composite material, the mass percentage of the polyvinylidene fluoride based polymer is 65-95%, the mass percentage of the modified molybdenum disulfide is 1-10%, and the mass percentage of the maleic anhydride grafted modified polypropylene is 0.5-15%.
5. A polyvinylidene fluoride-based dielectric composite film, characterized in that: The dielectric composite material is prepared according to any one of claims 1 to 4.
6. The polyvinylidene fluoride-based dielectric composite film according to claim 5, characterized in that: The dielectric composite material is prepared by melt blending and extrusion to obtain a polyvinylidene fluoride-based dielectric composite film.
7. A method for preparing a polyvinylidene fluoride-based dielectric composite film according to claim 5 or 6, characterized in that: include: The polyvinylidene fluoride based polymer, thermotropic liquid crystal polymer, maleic anhydride modified polypropylene and modified molybdenum disulfide with designed proportions are mixed and granulated, and then subjected to extrusion, stretching and casting treatment to obtain a dielectric composite film.
8. The method for preparing the polyvinylidene fluoride-based dielectric composite film according to claim 7, characterized in that: The preparation method of the modified molybdenum disulfide comprises: adding molybdenum disulfide into a hydrogen peroxide solution for surface hydroxylation treatment, then adding a γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent for ultrasonic treatment, and drying to obtain the modified molybdenum disulfide.
9. The method for preparing the polyvinylidene fluoride-based dielectric composite film according to claim 7, characterized in that: The mixing is carried out in a high-speed mixer, with the speed controlled at 80 to 300 r / ppm and the time being 1 to 5 minutes; And / or, the granulation is carried out in a twin-screw extruder, and the temperature of each zone is set as follows: the temperature of the first zone is: 110-140°C, the temperature of the second zone is: 150-180°C, the temperature of the third zone is: 170-230°C, and the temperature of the fourth zone is: 210-260°C.
10. The method for preparing the polyvinylidene fluoride-based dielectric composite film according to claim 7, characterized in that: The extrusion is carried out in a single-screw extruder, and the temperature of each zone is set as follows: the temperature of the first zone is 110-150°C, the temperature of the second zone is 150-200°C, the temperature of the third zone is 190-240°C, and the temperature of the fourth zone is 200-260°C; and / or, the stretching ratio is 1-8; and / or, the temperature of the casting roller in the casting process is 70-100°C.
Citation Information
Patent Citations
Novel easy-to-process fluorine-containing polymer dielectric composite material and preparation method thereof
CN118027582A
Cited By
PCR (Polymerase Chain Reaction) modified plastic applied to code scanner and preparation method of PCR modified plastic
CN120623744A